The representation of elementary student at cross-age about physics phenomenon - Anggoro, Subuh (Pennwell Publishing Co., 2020)
Naïve conceptions or misconception about the phenomenon of science are experienced by early childhood to adulthood and are not easy to change. The purpose of this study was to determine the conception of children aged 9-15 years about several scientific phenomena related to physics and biology. This research uses a survey method with a cross-sectional design. The research instrument was in the form of a three-tier conception test about the phenomenon of science. Participants answer questions online using Google Form. The data obtained include the participants' identities (name, gender, class, and school) and their answers to the problem of natural phenomena (true or false, confidence in the answers, and underlying reasons). The results showed that the majority of children aged 9-15 years experienced misconceptions about free fall, gravity in outer space, and sinking and floating. To be able to provide their conceptual change, one alternative learning strategy recommended is cognitive conflict aided by visual multimedia and supported by hands-on activities.